Utilization of MS-222 and Salt Solution on The Transportation of Jelawat (Leptobarbus hoevenii Blkr.) Fingerling - Hendry Yanto (Institut Pertanian Bogor, 2009)
The research about utilization of MS-222 and salt solution was conducted on the transportation of jelawat fingerling. The objective of this research was to find the optimum concentration of MS-222 (tricaine methanesulfonate) in water with similar salinity as transport medium of jelawat fingerling. These triplicate experiments consisted of 8 levels of MS-222 combined with NaCl; and the ratio of MS-222 (mg L-1) and salt (gL-1). Treatment A only salt 3 g L-1, without MS-222 in order to evaluate the important of salt in the transportation. Treatment B (MS-222 0.0; salt 3.0), C (10.0;3.0), D (20.0;3.0), E (30.0;3.0), F (40.0;3.0), G (50.0;3.0) and H (60.0;3.0). The size of jelawat were 10-12 cm in total length. the experimental unit, was a plastic bag filled with 1 L water, 3 L of oxygen and 25 fish. Those plastic bags had been placed in styrofoam box and transported by car for 18 hours. The results showed that the induction time, sedative duration and survival life of fish were significant (p < 0.05) among all those the treatments. The level of MS-222 40 mg L-1 and 50 mg L-1 were not different significantly (p > 0.05) difference on induction time, sedative duration and survival life. The best concentration of MS-222 was 40.02 mg L-1 for survival rate of jelawat fingerling transportation.Keywords: Tricaine Methanesulfonate, salt, transportation, and Leptobarbus hoevenii Blkr.